The Impact of the Digital Economy on Employment and Workforce Structure in Indonesia - Nestia Lianingsih; Dede Irman; Nurnisaa Nurnisaa (International Journal of Business, Economics, and Social Development, 2025)
This study examines the impact of the digital economy on employment and workforce structure in Indonesia. The digital economy in Indonesia is growing rapidly, driven by e-commerce, digital financial services, app-based transportation, and artificial intelligence-based technology, with a projected contribution of more than USD 130 billion by 2025. Using a mixed-method approach, this study analyzed data from 200 respondents consisting of workers in the digital economy sector and traditional sectors affected by digitalization, as well as in-depth interviews with 15 representatives of workers, business actors, and policy makers. The results showed that 68% of respondents considered the digital economy to increase job opportunities, although 40% of respondents admitted that digitalization also caused job losses in certain sectors. Changes in the workforce structure are seen in the increasing need for technology skills (45%), digital marketing (35%), and digital business management (30%). The main challenges faced by workers include lack of digital skills (50%), uncertain income (40%), and lack of social security (35%). This study recommends strengthening digital skills training programs through collaboration between the government and the private sector, developing regulations for protecting digital workers, and increasing financial inclusion for digital economy workers. This study contributes to a more comprehensive understanding of workforce transformation in the digital era and provides strategic input for policymakers in managing the workforce transition towards an inclusive and sustainable digital economy.